The Influence of Education and Training on Employee Performance Secretariat of the Regional People's Representative Council (DPRD) Barru Regency 2021 - 2024 - Hendrayani; Syahrir; Edi Jusriadi (LP2M IAIN Palopo, 2025)
The aim of this study is to determine the influence of education and training on the performance of employees of the Secretariat of the Regional People's Representative Council (DPRD) of Barru Regency. The analysis method used in this study is multiple linear regression analysis, T test, F test, correlation analysis and determination. The results of the study indicate that the hypothesis of Education on Employee Performance is accepted on the basis of the calculated T value of 2.516 which is greater than the T table value of 1.7340. In addition, the hypothesis of Training on Employee Performance is accepted on the basis of the calculated T value of 2.628 which is greater than the T table value of 1.7340. The results of the F test calculation show that Education and Training have a simultaneous effect on Employee Performance on the basis of the calculated F value of 14.789 which is greater than the F table value of 3.55. Then the results of the correlation coefficient test show that Education and Training on employee performance have a strong relationship, then based on the results of the determination test it shows that the contribution of Education and Training is 58% to the Employee Performance variable.